Assessment of Customer Value and Evaluation of Customer Equity - Nowak, Edward (Szacowanie wartości klienta i pomiar kapitału klienta, 2010)
Issues of customer value assessment are discussed from the perspective of customer relationship management concept. Advantages of customer relationship management are presented on the example of customer margin and net cash flows. Their respective values are used in evaluation of customer lifetime value and evaluation of customer equity. The relationships between customer profitability and customer costs are also presented.Keywords: customer relationship management, customer profitability,
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 121-131
Keywords: customer relationship management; customer profitability; customer value; customer equity